Sistem Aplikasi Kasir Berbasis Android Pada SMK Al-Huda Jatiagung - Siti Suliah; Selamet Samsugi; Neneng Neneng (Journal of Information Technology, Software Engineering and Computer Science, 2023)
The Al Huda Mart shop is one of the shops provided by the Al-Huda Jatiagung Foundation. The process of managing cashier data is still done manually, that is, it is recorded in a ledger and notes/receipts are provided and the price calculation is done manually so there are obstacles, namely the accumulation of books or notes. To solve this problem, in this research an Android-based cashier application system was built so that it can make it easier for cashiers to carry out sales transactions, namely the ordering process, payment process and sales reports. This research uses extreme programming development methods and is designed using UML. This system uses the Javascript programming language. Implementation uses the Xampp and MySQL applications. The result of this research is an Android-based cashier application system that can carry out sales transactions, starting from ordering goods, paying, and displaying sales reports. Based on the results of ISO 25010 testing which was carried out involving 5 respondents consisting of cashiers and customers. It can be concluded that the resulting software is suitable for use. Percentage of success with total Functionality testing 98.40%, Usability testing 95.20% and Reability testing 90.00%. Respondents stated that the construction of this application system could help cashiers and customers in managing sales at Al Huda Mart stores.